If ( a + b ) ( b + c ) ( c + a ) ( a − b ) ( b − c ) ( c − a ) = 2 0 1 1 2 0 1 0 , then what is a + b a + b + c b + c + a c ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Given that
( a + b ) ( b + c ) ( c + a ) ( a − b ) ( b − c ) ( c − a ) a b 2 + b c 2 + c a 2 + a 2 b + b 2 c + c 2 a + 2 a b c a b 2 + b c 2 + c a 2 − a 2 b − b 2 c − c 2 a ∑ a b 2 + ∑ a 2 b + 2 a b c ∑ a b 2 − ∑ a 2 b 2 0 1 1 ∑ a b 2 − 2 0 1 1 ∑ a 2 b ⟹ ∑ a b 2 = 2 0 1 1 2 0 1 0 = 2 0 1 1 2 0 1 0 = 2 0 1 1 2 0 1 0 = 2 0 1 0 ∑ a b 2 + 2 0 1 0 ∑ a 2 b + 4 0 2 0 a b c = 4 0 2 1 ∑ a 2 b + 4 0 2 0 a b c
Then we have:
a + b a + b + c b + c + a c = ∑ a b 2 + ∑ a 2 b + 2 a b c ∑ a b 2 + 2 ∑ a 2 b + 3 a b c = 4 0 2 2 ∑ a 2 b + 4 0 2 2 a b c 4 0 2 3 ∑ a 2 b + 4 0 2 3 a b c = 4 0 2 2 4 0 2 3 ≈ 1 . 0 0 0 2 5
Thank you for the solution
Note: This is a cheeky solution:) Pick a = 0 , so we have b + c c − b = 2 0 1 1 2 0 1 0 ⟹ c = 4 0 2 1 b then it is suffices to compute b + c b + 1 = 4 0 2 2 1 + 1 = 4 0 2 2 4 0 2 3
How about assuming a/b, b/c, c/a as alpha 1 2 and 3 respectively. Where they are roots of cubic eqn [(x-1)/(x+1)]3. Then apply transformation of roots and find sigma of 1/(1+1/x).
There are in fact three solutions to the first equation. Unfortunately, none of solutions determine fixed values for the variables. Fortunately, all three solutions, when substituted into the second equation and the resultant expression is simplified, the same determined value results: 4 0 2 2 4 0 2 3 ≈ 1 . 0 0 0 2 4 8 6 3 2 5 2 1 1 3 3 7 6 4 2 9 6 3 6 9 9 6 5 1 9 1 4 4 7 0 4 1 2 7 2 9 9 8 5 0 8 2 0 4 9 .
The three solutions:
{ b → 4 0 2 1 a , c → 0 } , { c → 2 ( 4 0 2 1 a − b ) − 1 6 1 8 4 5 2 6 a 2 b 2 − 6 4 6 8 1 8 0 4 a 3 b + a 4 + 3 2 3 2 8 8 3 6 a b 3 + 1 6 1 6 8 4 4 1 b 4 + a 2 − 4 0 2 0 a b − 4 0 2 1 b 2 } , { c → 2 ( 4 0 2 1 a − b ) 1 6 1 8 4 5 2 6 a 2 b 2 − 6 4 6 8 1 8 0 4 a 3 b + a 4 + 3 2 3 2 8 8 3 6 a b 3 + 1 6 1 6 8 4 4 1 b 4 + a 2 − 4 0 2 0 a b − 4 0 2 1 b 2 }
When solving the expressions, the variables were assumed to be complex.
Problem Loading...
Note Loading...
Set Loading...
χ : = ( a + b ) ( b + c ) ( c + a ) ( a − b ) ( b − c ) ( c − a ) = 2 0 1 1 2 0 1 0
χ is an improper fraction, where both the numerator and the denominator are polynomials of degree 3 . So,
( a + b ) ( b + c ) ( c + a ) ( a − b ) ( b − c ) ( c − a ) ≡ P + a + b A + b + c B + c + a C
To get A , multiply the above equation by ( a + b ) and set b = − a .
P ( a + b ) + A + b + c B ( a + b ) + c + a C ( a + b ) ⟹ A ∴ A = ( b + c ) ( c + a ) ( a − b ) ( b − c ) ( c − a ) = ( − a + c ) ( c + a ) ( a + a ) ( − a − c ) ( c − a ) = − 2 a
Similarly, B = − 2 b , C = − 2 c
To get P , multiply the equation by ( a + b ) ( b + c ) ( c + a ) and set a = b = c .
P ( a + b ) ( b + c ) ( c + a ) + A ( b + c ) ( c + a ) + B ( a + b ) ( c + a ) + C ( a + b ) ( b + c ) P ( a + b ) ( b + c ) ( c + a ) − 2 a ( b + c ) ( c + a ) − 2 b ( a + b ) ( c + a ) − 2 c ( a + b ) ( b + c ) P ( 8 c ) − 8 c − 8 c − 8 c ⟹ P = ( a − b ) ( b − c ) ( c − a ) = ( a − b ) ( b − c ) ( c − a ) = 0 = 3
Therefore,
( a + b ) ( b + c ) ( c + a ) ( a − b ) ( b − c ) ( c − a ) χ ⟹ a + b a + b + c b + c + a c = 3 − a + b 2 a − b + c 2 b − c + a 2 c = 3 − 2 ( a + b a + b + c b + c + a c ) = 2 3 − χ = 2 3 − 2 0 1 1 2 0 1 0 = 4 0 2 2 4 0 2 3